The active role of spermatozoa in transgenerational inheritance. Issue 1909 (28th August 2019) - Sciamanna, Ilaria; Serafino, Annalucia; Shapiro, James A.; Spadafora, Corrado
Abstract : The active uptake of exogenous nucleic acids by spermatozoa of virtually all animal species is a well-established phenomenon whose significance has long been underappreciated. A growing body of published data demonstrates that extracellular vesicles released from mammalian somatic tissues pass an RNA-based flow of information to epididymal spermatozoa, thereby crossing the Weismann barrier. That information is delivered to oocytes at fertilization and affects the fate of the developing progeny. We propose that this essential process of epigenetic transmission depends upon the documented ability of epididymal spermatozoa to bind and internalize foreign nucleic acids in their nuclei. In other words, spermatozoa are not passive vectors of exogenous molecules but rather active participants in essential somatic communication across generations.